The Influence Of Education And Entrepreneurship Skills On Business Sustainability; Self-Efficacy as an Intervening Variable In Tourism Service Business - Dhian Tyas Untari (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Huge business opportunities are created from tourism development in Bekasi. Bekasi is one of the buffer zones for the Capital City, which has a large population and a very high commuter population, creating a business opportunity for the tourism service sector. Thus, it is important to analyze further how entrepreneurship education and entrepreneurial skills influence business Sustainability with self-efficacy as an intervening variable for tourism service entrepreneurs in Bekasi. This type of research uses a quantitative approach by surveying respondents who are tourism service entrepreneurs in Bekasi City, West Java, who are members of social media groups. Respondents involved in the study were 41 people. The data analysis technique in this study is quantitative data analysis, namely testing and analyzing data by calculating numbers and then drawing conclusions from the test by testing. a) Classical Assumptions, namely normality test, linearity test, multicollinearity test, heteroscedasticity test b) Path analysis c) Significance test. The results of the study show that Entrepreneurship Education and Entrepreneurial Skills are very important in increasing Self-efficacy, which will impact Business sustainability.